Analysis of Teacher Education Patterns in Supporting the Religious Development of Children with Special Needs at Nurul Qodiri Integrated Islamic Middle School - Amanatun Nafiah; Ehwanudin; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to analyze the teaching patterns of teachers in supporting the religious development of children with special needs (autism) in Fiqh learning for third-grade students at MIS Terpadu Nurul Qodiri. The background of this study is based on the important role of teachers in inclusive education, especially in guiding children with autism who have different characteristics and learning needs compared to regular students. This research employed a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation.The results of the study indicate that the teaching patterns applied by teachers are adaptive and individualized, using personal approaches, visual media, direct practice, and repetition of material to enhance students’ understanding. In addition, teachers simplify the learning materials and provide intensive guidance according to the needs of children with autism. The religious development of students is reflected in three aspects: cognitive (understanding simple Fiqh materials), psychomotor (ability to perform worship practices such as ablution and prayer), and affective (religious attitudes developed through habituation and teacher modeling).In conclusion, the teaching patterns of teachers play a significant role in supporting the religious development of children with special needs. Appropriate, flexible, and student-centered teaching patterns can gradually improve the understanding and practice of religious values among students with autism.